Construction of heterogeneous interfaces on Ti3AlC2 micro-particles via surface dotting liquid metal to enhance electromagnetic wave absorption performance - Zhao, Kun-Yan; Luo, Cheng-Long; Sun, Chang; Huang, Ming-Lu; Wang, Ming (Composites. Part A, Applied science and manufacturing, 2023)
[Display omitted] •Liquid metal anchoring Ti3AlC2 particles have heterointerfaces and heterojunctions.•Heterointerfaces enhanced interface polarization and dipole polarization greatly.•The hybrid particles exhibit excellent microwave absorption performance.•An effective absorption bandwidth of 7.2 GHz is achieved by the hybrid particles. MAX phase (Ti3AlC2) and its derivative MXene has brought the development of electromagnetic shielding and absorbing materials into a new stage. Herein, the MAX phase was creatively used to prepare microwave absorbing materials. The Ti3AlC2/liquid metal (TLM) hybrid micro-particles with multiple heterogeneous interfaces were prepared by simply liquid metal (LM) dotting on Ti3AlC2 surface and annealing at high temperature. When the mass fraction of liquid metal is 35 wt% and the sample is annealed for 2 h, the reflection loss (RL) value is −36.07 dB, and the maximum effective absorption bandwidth (EAB) is 7.2 GHz at a thickness of 2.5 mm. The electromagnetic wave loss ability of the TLM hybrid micro-particles comes from its special heterostructures, including multiple interfaces and defects caused by liquid metal etching.